(untitled) (Research, Society and Development, 2021)
Pandemic and consequently social isolation have brought to light the current education scenario in the country. Teachers and students had to adapt to remote activities where technology is needed to cause the least possible damage to learning. Technology and its increasing dissemination provide the growth of online education by adapting teachers and students to this new education resource. Teaching and learning online requires a lot of commitment on the part of both students and educators. Students need a certain degree of responsibility and commitment with regard to organizing study time and carrying out tasks, whereas teachers need to have time to attend to students and availability to access the virtual environment. Remote education is a recent topic, so any study in the area and in-depth study of this topic is valid. The objective of this study is to discuss teacher training in the face of the use of technologies in the face of changes imposed by the current reality. The data for this qualitative approach study were collected in a message group created to assist students and teachers during remote activities in the circulation of the New Coronavirus. Nineteen teachers and 33 students from a public school in the interior of Rio Grande do Sul participated in this study. Data were collected in the month of June 2020. Content analysis was used, using Bardin’s theoretical framework. It was found that teaching remotely using technology is possible. A number of factors contributed to the difficulties faced by teachers and students in adapting to remote activities. Among them we can highlight: the lack of time to adapt and prepare for the use of technology, the lack of access to technology, since many students do not have access to quality internet and use their cell phones to access the Learning Platform and the groups of support. The lack of mastery and technological knowledge on the part of teachers and the lack of investments in technology in schools make teaching practice challenging, due to the changes imposed by the period of social isolation, signaling that the educational changes achieved are maintained after the passage this delicate phase.